Validity of Wetland-Based Chemistry Teaching E-Module with SCCrT Model Assisted with Liveworksheet to Improve Students' 6c Skills - Rusmansyah; Abdul Hamid; Parham Saadi; Mahdian; Mohamad Nor Aufa; Lukman Abdul Rauf Laliyo (Jurnal Penelitian Pendidikan IPA, 2025)
Anticipating a less-than-optimal learning process to facilitate students in developing 6C Skills, it is necessary to develop wetland-based teaching E-modules using the Scientific Critical Creative Thinking (SCCrT) model with the help of Liveworksheets. This study aims to analyze the validity of a wetland-based chemistry teaching e-module using the SCCrT model assisted by Liveworksheets to enhance students' 6C skills. This research and development (R&D) study uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), focusing on the Analysis, Design, and Development stages. The research method employed is qualitative with a descriptive approach. Data was collected through a validation process in which five expert validators filled out a validation sheet. This process aimed to gather valuable feedback on the design and development of the e-module being created. The validation results were then analyzed using a Likert scale, and they indicated that the module is highly valid based on content, presentation, language, and media. Based on these findings, it can be concluded that the wetland-based chemistry e-learning module with the SCCrT model, supported by Liveworksheets, has proven to be valid and is highly feasible for use in improving students' 6C skills in an effective way.